Graffiti friendships and existential visual sociology - Jacobson, Malcolm (Street Art & Urban Creativity, 2020)
The aim of this paper is to utilize photographs to investigate existential aspects of graffiti that are theoretically underdeveloped such as how the subculture offers foundation for life-long friendships. Previous literature on the life of graffiti writers has often emphasized aspects of hyper masculinity such as competition, bravery, law breaking and risk behavior and neglected how boundaries concerning space and generations are negotiated through graffiti writing.